Importance of Clinical and Laboratory Findings in the Diagnosis and Surgical Prognosis of Patients with Constrictive Pericarditis - Fernandes,Fábio (2017)
Abstract Background: International studies have reported the value of the clinical profile and laboratory findings in the diagnosis of constrictive pericarditis. However, Brazilian population data are scarce. Objective: To assess the clinical characteristics, sensitivity of imaging tests and factors related to the death of patients with constrictive pericarditis undergoing pericardiectomy. Methods: Patients with constrictive pericarditis surgically confirmed were retrospectively assessed regarding their clinical and laboratory variables. Two methods were used: transthoracic echocardiography and cardiac magnetic resonance imaging. Mortality predictors were determined by use of univariate analysis with Cox proportional hazards model and hazard ratio. All tests were two-tailed, and an alpha error ≤ 5% was considered statically significant. Results: We studied 84 patients (mean age, 44 ± 17.9 years; 67% male). Signs and symptoms of predominantly right heart failure were present with jugular venous distention, edema and ascites in 89%, 89% and 62% of the cases, respectively. Idiopathic etiology was present in 69.1%, followed by tuberculosis (21%). Despite the advanced heart failure degree, low BNP levels (median, 157 pg/mL) were found. The diagnostic sensitivities for constriction of echocardiography and magnetic resonance imaging were 53.6% and 95.9%, respectively. There were 9 deaths (10.7%), and the risk factors were: anemia, BNP and C reactive protein levels, pulmonary hypertension >55 mm Hg, and atrial fibrillation. Conclusions: Magnetic resonance imaging had better diagnostic sensitivity. Clinical, laboratory and imaging markers were associated with death.